Association between material and design used in a ureteral stent with complication in ureteral catheterisation: A systematic review - Pakpahan, Karimul Abdi; Birowo, Ponco; Rasyid, Nur; Atmoko, Widi (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
The double-J stent is one of the ureteral catheters with curved ends for fixation. Since its introduction in 1978, catheterisation using a double-J stent has become one of the most frequently performed procedures in urology. However, double-J stents may lead to various complications, causing patient discomfort, pain, and bladder symptoms. Technological advancements in stent design aim to minimise these complications and enhance comfort. This review aimed to determine the association between the material and design used in ureteral stents and complications in ureteral catheterisation. We conducted a systematic review following the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) checklist. Screening based on specific inclusion criteria was employed to select potential studies. A database search yielded a total of 124 studies. Nine full texts were evaluated for eligibility, resulting in the exclusion of one paper. Our findings indicate that ureteral stent insertion significantly increases the frequency of pain and urinary symptoms while decreasing overall health. The choice of materials and design plays a crucial role in minimising pain and improving the quality of life for patients. Physical properties such as firmness and tensile strength also affect the quality of life, with higher firmness and tensile strength causing lower quality of life. Stent material and design choice were context-dependent. Using soft stents and specialised soft distal pigtails has been shown to reduce patient stent-related symptoms. Silicone stents showed the least bladder symptoms than polymeric stents. Polymeric stents also showed no difference in utility from metallic stents for long-term usage.